واقع العرض السياحي في محافظة اللاذقية في ظل الأزمة الراهنة (2017-2011) - صقر, محمد; سلمان, حيان; عباس, لورا (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The Research aims to study tourism supply in Lattakia Governorate, This supply includes various attractions (natural, cultural, historical, restaurants, hotels, etc.). The study also dealt with an important problem: Is the current crisis affected negatively on the supply of tourism product in various components in the province of Lattakia. The study also includes the study of the tourism offer before the current crisis period. Methodology: analytical descriptive. The most important findings of the research: The negative effects of the current crisis on all components of the tourism offer, which led to a decline in the tourism and decrease in tourism supply in terms of quantity and quality, which in turn led to a significant impact on tourism industry. Meeting the current challenges and reducing the negative effects of the current crisis on the tourism offer requires great efforts and huge financial resources, in addition to providing a clear political and developmental vision for the tourism sector within the framework of regional planning. يتناول البحث دراسة العرض السياحي في محافظة اللاذقية، وما يتضمنه هذا العرض من عوامل جذب مختلفة (طبيعية، ثقافية، تاريخية، مطاعم، فنادق.الخ). كما تناول البحث مشكلة هامة وهي: هل أثرت الأزمة الراهنة بشكل سلبي على عرض المنتج السياحي بمختلف مكوناته في محافظة اللاذقية. كما يتضمن البحث دراسة العرض السياحي قبل فترة الأزمة الراهنة. المنهج المتبع: الصفي التحليلي. أهم النتائج التي توصل لها البحث: الآثار السلبية للأزمة الراهنة على كافة مكونات العرض السياحي مما ادى إلى حدوث تراجع ملحوض وانخفاض في العرض السياحي من حيث الكم والنوع، والذي ادى بدوره إلى تأثر الصناعة السياحية بشكل كبير. إن مواجهة التحديات الحالية والتقليل من الآثار السلبية للأزمة الراهنة على العرض السياحي يتطلب جهوداً كبيرة وإمكانيات مادية ضخمة، بالإضافة إلى توفر رؤية سياسية تنموية واضحة لقطاع السياحة في إطار التخطيط الإقليمي.